Perancangan UI/UX Pada Aplikasi Elaruna Dengan Metode Design Thinking - Fellycia Caroline; Steffanie Angelica; Muhammad Fajar Ariansyah; Serenity Devina Suryanto; Muhammad Rizky Pribadi (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Indonesia has great potential in the tourism sector due to its rich culture and natural beauty, but it still faces challenges in the form of limited access to integrated and reliable information for tourists. This study aims to design a mobile-based tourism information application user interface (UI/UX) that provides quick, accurate, and user-friendly access to information. The method used is Design Thinking, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. The design process was carried out using a user-centered approach to ensure the design meets the needs and preferences of tourists. Test results show that most users find the application interface easy to use, visually appealing, and clearly navigable, with 91.3% of respondents stating that the navigation is easy and 73.9% feeling that the application runs smoothly. This demonstrates that the Design Thinking approach is effective in producing design solutions that are responsive to user needs. This study is expected to contribute to the development of digital tourism applications in Indonesia and serve as a foundation for further research in the development of features and broader integration of information technology.